Investigation of the essential oil from the peels of the fruit of Citrus reticulata Blanco var. szinkom - Condeno-Santelices, Cielo P.
The fresh outer rind of the non-artifically colored mature fruit of Citrus reticulate Blanco var. szinkom was subjected to distillation using the Clevenger Apparatus for oils lighter than water. The volatile oil content was found to be 4.5%. The moisture content was found to be 69.8%.